IDYLLIC “KEY” TO THE POETRY OF M. LERMONTOV (Proceedings of Southern Federal University. Philology, 2014)
The Poetry of M. Lermontov neither by contemporaries nor subsequent researchers is not associated with the genre of idylls. In the foreground of perception for Lermontov’s time were historically new “civil” poems, which, having arisen out of Byronism, paving the way for a new poetic era. On the other hand, the genre idyll was one of the “victims” of the changes in the consciousness of the genre that came to the 1820s. The paper attempts to outline the previously rarely distinguished by researchers in the poetry of Mikhail Lermontov genre of idyllic space, and also to show the importance of the genre in the art world of the poet. The authors conducted a genre analysis of a number of classic poems “How often surrounded by a motley crowd.”, “When the waves yellowing cornfield.”, “I go out alone on the road.”, “Homeland” etc. arguing that the genre elements of idyll play important for the understanding of the poetics by Lermontov.Key words: historical poetics, Russian poetry, genre analysis, motif, idyll, elegy, Lermontov.